Effects of feeding different dietary net energy levels to growing-finishing pigs when dietary lysine is adequate - Nitikanchana, Sureemas; Dritz, Steven S.; Tokach, Michael D.; DeRouchey, Joel M.; Goodband, Robert D.; White, Bradley J. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2015)
A total of 543 pigs (PIC 1050 × 327: PIC Hendersonville, TN) were used in 2 consecutive experiments with initial BW of 105 and 125 lb in Experiments 1 and 2, respectively. The objective was to validate the regression equations predicting growth rate and feed efficiency of growing-finishing pigs based on dietary NE content by comparing actual and predicted performance. Thus, the 5 treatments included diets with: (1) 30% dried distillers grains with solubles (DDGS), 20% wheat middlings, and 4 to 5% soybean hulls (low-energy); (2) 20% wheat middlings and 4 to 5% soybean hulls (low-energy); (3) a corn-soybean meal diet (medium-energy); (4) diet 2 supplemented with 3.7% choice white grease (CWG) to equalize NE level to diet 3 (medium-energy); and (5) a corn-soybean meal diet with 3.7% CWG (high-energy). In Experiments 1 and 2, increasing dietary NE increased (linear, P < 0.01) final weight, ADG, and improved feed efficiency but decreased (P < 0.11) ADFI. Only small differences were observed between the predicted and observed values of ADG and feed efficiency, except for the low-energy diet containing the highest fiber content (30% DDGS, wheat middlings and soy hulls; diet 1). Carcass weight and carcass yield increased (linear, P = 0.01) with increasing dietary NE. Also, backfat depth increased (linear, P = 0.01), loin depth decreased (quadratic, P = 0.05), and lean percentage decreased (linear, P = 0.01) with increasing dietary NE (linear, P = 0.01). Jowl iodine value (IV) also decreased with increasing dietary NE. No differences (P > 0.26) in net energy caloric efficiency (NEE) on a live weight basis were observed with increasing dietary NE. Nevertheless, feeding 30% DDGS (diet 1) resulted in a poorer (P = 0.05) NEE on a carcass basis compared with feeding the other diets. In conclusion, the prediction equations provided a good estimate of growth rate and feed efficiency of growing-finishing pigs fed different levels of dietary NE except for the pigs fed low-energy diet containing highest fiber content (diet 1). These predictions of growth performance can be used to model the economic value of different dietary energy strategies.
Swine Industry Day, 2014 is known as Swine Day, 2014
Keywords: Growth; Growing-finishing pig; Net energy; Regression